Facilitating Effects of Emotion on the Perception of Biological Motion: Evidence for a Happiness Superiority Effect. (June 2017) - Lee, Hannah; Kim, Jejoong
It has been reported that visual perception can be influenced not only by the physical features of a stimulus but also by the emotional valence of the stimulus, even without explicit emotion recognition. Some previous studies reported an anger superiority effect while others found a happiness superiority effect during visual perception. It thus remains unclear as to which emotion is more influential. In the present study, we conducted two experiments using biological motion (BM) stimuli to examine whether emotional valence of the stimuli would affect BM perception; and if so, whether a specific type of emotion is associated with a superiority effect. Point-light walkers with three emotion types (anger, happiness, and neutral) were used, and the threshold to detect BM within noise was measured in Experiment 1. Participants showed higher performance in detecting happy walkers compared with the angry and neutral walkers. Follow-up motion velocity analysis revealed that physical difference among the stimuli was not the main factor causing the effect. The results of the emotion recognition task in Experiment 2 also showed a happiness superiority effect, as in Experiment 1. These results show that emotional valence (happiness) of the stimuli can facilitate the processing of BM.